The formation of a failed continental breakup basin: The Cenozoic development of the Faroe‐Shetland Basin. (19th April 2013) - Fletcher, Rosie; Kusznir, Nick; Roberts, Alan; Hunsdale, Robert
Abstract: Ultra‐large rift basins, which may represent palaeo‐propagating rift tips ahead of continental rupture, provide an opportunity to study the processes that cause continental lithosphere thinning and rupture at an intermediate stage. One such rift basin is the Faroe‐Shetland Basin (FSB) on the north‐east Atlantic margin. To determine the mode and timing of thinning of the FSB, we have quantified apparent upper crustal β‐factors (stretching factors) from fault heaves and apparent whole‐lithosphere β‐factors by flexural backstripping and decompaction. These observations are compared with models of rift basin formation to determine the mode and timing of thinning of the FSB. We find that the Late Jurassic to Late Palaeocene (pre‐Atlantic) history of the FSB can be explained by a Jurassic to Cretaceous depth‐uniform lithosphere thinning event with a β‐factor of ~1.3 followed by a Late Palaeocene transient regional uplift of 450–550 m. However, post‐Palaeocene subsidence in the FSB of more than 1.9 km indicates that a Palaeocene rift with a β‐factor of more than 1.4 occurred, but there is only minor Palaeocene or post‐Palaeocene faulting (upper crustal β‐factors of less than 1.1). The subsidence is too localized within the FSB to be caused by a regional mantle anomaly. To resolve the β‐factor discrepancy, we propose that the lithospheric mantle and lower crust experienced a greater degree of thinning than the upper crust. Syn‐breakup volcanism within the FSB suggests that depth‐dependent thinning was synchronous with continental breakup at the adjacent Faroes and Møre margins. We suggest that depth‐dependent continental lithospheric thinning can result from small‐scale convection that thins the lithosphere along multiple offset axes prior to continental rupture, leaving a failed breakup basin once seafloor spreading begins. This study provides insight into the structure and formation of a generic global class of ultra‐large rift basins formed by failed continental breakup.